The mineralogy of gold-copper skarn related porphyry at the Batu Hijau deposit, Sumbawa, Indonesia - May Thwee Aye; Subagyo Pramumijoyo; Arifudin Idrus; Lucas Donny Setijadji; Akira Imai; Naoto Araki; Johan Arif (Geological Engineering Department Universitas Gadjah Mada, 2015)
Clacic gold-copper bearing skarn in the Batu Hijau porphyry deposit is located in the western part of Sumbawa Island, Indonesia. Skarn mineralizations were found at the deep level of the deposit (-450m to -1050mL) by drilling program 2003. No evidence around Batu Hijau has limestone although most skarn are metasomatiz ed from carbonate-rich rock as limestone or marble. Most skarn-type metasomatic alteration and mineralization occurs at the contact of andesitic volcanic rock and intermediate tonalite porphyry intrusion and within intermediate tonalite in some. Although both endoskarn and exoskarn can be developed, it has no clear minerals to known the endoskarn. Exoskarn is more principle skarn zone. The formation of skarn occurred two min stages: (1) prograde and (2) retrograde. The prograde stage is temporally and spatially divided into two sub-stages as early prograde (sub-stage I) and prograde metasomatic (sub-stage II). Sub-stage I begin immediately after the intrusion of the tonalite stock into the calcium rich volcanic rocks. Then, sub-stage II originated with segregation and evolution of a fluid phase in the pluton and its invasion into fractures and micro-fractures of host rocks developed during sub-stage I. The introduction of considerable amount of Fe, Si and Mg led to the large amounts of medium- to coarse-grained anhydrous calc-silicates. From the texture and mineralogy, the retrograde metasomatic stage can be divided into two sub-stages: (a) early retrograde and (sub-stage III) and (b) late retrograde (sub-stage IV). During sub-stage III, the previously formed skarn zones were affected by intense multiple hydro-fracturing phases in the gold-copper bearing stocks. Therefore, the considerable amounts of hydrous calc-silicates (epidote), sulfides (pyrite, chalcopyrite, sphalerite), oxides (magnetite, hematite) and carbonates (calcite) replaced the anhydrous calc-silicates. Sub-stage IV was coexisting with the intrusion of relatively low temperature, more highly oxidizing fluids into skarn system, bringing about partial alteration of the early-formed calc-silicates and developing a series of very fine-grained aggregrates of chlorite, clay, hematite and calcite.